2008
DOI: 10.2174/138161208783597380
|View full text |Cite
|
Sign up to set email alerts
|

Cerebroprotective Functions of HO-2

Abstract: The constitutive isoform of heme oxygenase, HO-2, is highly expressed in the brain and in cerebral vessels. HO-2 functions in the brain have been evaluated using pharmacological inhibitors of the enzyme and HO-2 gene deletion in in vivo animal models and in cultured cells (neurons, astrocytes, cerebral vascular endothelial cells). Rapid activation of HO-2 via posttranslational modifications without upregulation of HO-2 expression or HO-1 induction coincides with the increase in cerebral blood flow aimed at mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
82
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 157 publications
3
82
0
Order By: Relevance
“…1 Endogenously produced CO has cytoprotective functions in the cardiovascular system that include antiapoptotic, antioxidant, and antiinflammatory influences. [1][2][3][4][5] Gaseous CO, administered at low concentrations, provides an effective treatment for diseases characterized by oxidative stress and inflammation. 1,5 The effects of gaseous CO can be reproduced by CO donors, termed CO-releasing molecules (CORMs).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 Endogenously produced CO has cytoprotective functions in the cardiovascular system that include antiapoptotic, antioxidant, and antiinflammatory influences. [1][2][3][4][5] Gaseous CO, administered at low concentrations, provides an effective treatment for diseases characterized by oxidative stress and inflammation. 1,5 The effects of gaseous CO can be reproduced by CO donors, termed CO-releasing molecules (CORMs).…”
Section: Introductionmentioning
confidence: 99%
“…5 In the cerebral circulation, endogenously produced CO is a physiologically relevant dilator regulator of cerebral blood flow, 6 and a potent antioxidant and antiapoptotic compound. 3,7,8 Previously, we have showed that CORM-A1 [Na 2 (H 3 BCO 2 )], a water-soluble compound that slowly releases gaseous CO in physiologic solutions, is a convenient tool to investigate the biologic effects of CO in in vivo and in vitro studies related to the mechanism of cerebral vascular survival during oxidative stress and inflammation. 3,8,9 CORM-A1 reduces formation of reactive oxygen species, prevents apoptosis, and promotes survival of cerebral vascular endothelial cells exposed to the excitotoxic neurotransmitter glutamate and a proinflammatory cytokine TNF-α.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations